2012
DOI: 10.1016/j.socscimed.2011.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to use ADHD treatments: A mixed methods study of perceptions by adolescents, parents, health professionals and teachers

Abstract: Little is known about factors that influence willingness to engage in treatment for attention deficit/hyperactivity disorder (ADHD). From 2007 to 2008, in the context of a longitudinal study assessing ADHD detection and service use in the United States, we simultaneously elicited ADHD treatment perceptions from four stakeholder groups: adolescents, parents, health care professionals and teachers. We assessed their willingness to use ADHD interventions and views of potential undesirable effects of two pharmacol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
164
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(173 citation statements)
references
References 40 publications
5
164
1
3
Order By: Relevance
“…51,52,54,57 Bussing et al used a mixedmethods approach combining vignette responses and open-ended answers to study ADHD treatment willingness and perceptions of undesirable treatment side effects among four stakeholder groups for ADHD treatment of adolescents, namely 148 youth, 161 caregivers, 132 healthcare providers, and 122 teachers. 57 Stigma associated with medication and behavioral therapies emerged as a significant treatment barrier in the qualitative analysis. The study also demonstrated that adolescents were significantly less willing than adults to consider medication or psychosocial treatments for ADHD.…”
Section: Public Stigmamentioning
confidence: 99%
See 3 more Smart Citations
“…51,52,54,57 Bussing et al used a mixedmethods approach combining vignette responses and open-ended answers to study ADHD treatment willingness and perceptions of undesirable treatment side effects among four stakeholder groups for ADHD treatment of adolescents, namely 148 youth, 161 caregivers, 132 healthcare providers, and 122 teachers. 57 Stigma associated with medication and behavioral therapies emerged as a significant treatment barrier in the qualitative analysis. The study also demonstrated that adolescents were significantly less willing than adults to consider medication or psychosocial treatments for ADHD.…”
Section: Public Stigmamentioning
confidence: 99%
“…The study also demonstrated that adolescents were significantly less willing than adults to consider medication or psychosocial treatments for ADHD. 57 One vignette study sought to explore the impact of diagnostic/psychiatric labeling on the attitudes and behavioral intentions of school-age children towards a hypothetical peer presenting with ADHD symptoms. 52 Law et al recruited 120 children from schools in the UK and found that the majority of participants held predominantly negative attitudes towards the vignette child with ADHD symptoms, with no additional effect of diagnostic/psychiatric labeling on children's attitudes and social behavioral intentions.…”
Section: Public Stigmamentioning
confidence: 99%
See 2 more Smart Citations
“…22 A su vez, una reciente investigación en el sureste de Estados Unidos demostró que los maestros de adolescentes con TDAH estaban dispuestos a que los alumnos recibieran tratamiento psicosocial y farmacológico. 23 La información acerca de los conocimientos y creencias de los maestros sobre el TDAH en Latinoamérica es escasa. Un estudio realizado en Puerto Rico evaluó los conocimientos sobre la enfermedad en 132 maestros de escuelas pú-blicas y privadas, donde 35% reportó tener conocimientos previos respecto al TDAH y 72% mostró un nivel bajo de conocimientos.…”
unclassified